A UNIFIED APPROACH TO SOLVABILITY CONDITIONS FOR NONLINEAR SECOND-ORDER ELLIPTIC EQUATIONS AT RESONANCE - RUNST, THOMAS (The Bulletin of the London Mathematical Society, 1999)
It is shown that known solvability conditions and several new existence results for semilinear elliptic boundary value problems at resonance can be considered from a unified point of view. The proofs apply Leray–Schauder degree arguments. 1991 Mathematics Subject Classification 35J65, 47H11, 47H15.